2020
DOI: 10.1007/s12549-020-00442-3
|View full text |Cite
|
Sign up to set email alerts
|

The Devonian/Carboniferous boundary interval in Poland: multidisciplinary studies in pelagic (Holy Cross Mountains and Sudetes) and ramp (Western Pomerania) successions

Abstract: A multidisciplinary study of the Devonian–Carboniferous boundary interval in pelagic successions of the Holy Cross Mountains and Sudetes and the ramp successions in the Western Pomerania region (Poland) is presented herein. The analysis applies the results of new palaeontological and biostratigraphic studies based mainly on conodonts, ammonoids and palynomorphs, biostratigraphic results interpreted earlier by different authors that have been re-examined, and geochemical and mineralogical characteristics, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 74 publications
(211 reference statements)
1
7
0
Order By: Relevance
“…6: see nos. 9 and 10) may also be significant here, and at Dzikowiec (Matyja et al, 2021). The higher miospore concentration was previously noticed in the topmost Devonian (European standard lepidophyta-nitidus (LN) Miospore Zone) from the Kowala Quarry (Filipiak and Racki, 2010), and other regions (Prestianni et al, 2016;Marshall et al, 2020).…”
Section: Palynomorphssupporting
confidence: 59%
See 1 more Smart Citation
“…6: see nos. 9 and 10) may also be significant here, and at Dzikowiec (Matyja et al, 2021). The higher miospore concentration was previously noticed in the topmost Devonian (European standard lepidophyta-nitidus (LN) Miospore Zone) from the Kowala Quarry (Filipiak and Racki, 2010), and other regions (Prestianni et al, 2016;Marshall et al, 2020).…”
Section: Palynomorphssupporting
confidence: 59%
“…6: see nos. 1-8), are only dubiously attributed to this species, this taxonomic interpretation is strengthened by the occurrence of the guide species in the Hangenberg Black Shale (HBS) in another D-C boundary section in the Bardo Unit (Wapnica quarry at Dzikowiec village in Kłodzko County, Matyja et al, 2021;Fig. 6: see nos.…”
Section: Palynomorphsmentioning
confidence: 98%
“…1). Studies by Girard et al (2014) and Aretz (2020) indicated relative stability in extinction rates of marine organisms, and carbon isotope curves published by Buggisch & Joachimski (2006) and Matyja et al (2021) indicate no major pertubations in the global carbon cycle.…”
Section: Hangenberg Pre-crisis (Ct69-7 To Ct70-a)mentioning
confidence: 99%
“…Firstly, anoxic conditions sometimes persist into the lower Tournaisian (Paschall et al 2019). And secondly, corresponding negative carbon isotope excursions (NCIEs) are recognized preceding the HBS in the upper praesulcata zone / lower costatus-kockeli interregnum zone and Devonian/Carboniferous Boundary (DCB) (Matyja et al 2020;Pisarzowska & Racki, 2020;.…”
Section: Introductionmentioning
confidence: 99%